FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2012-2014 (Students' Journal of Accounting and Banking, 2015)
The capital struktur modal is a balance between the use of equity capital with the use of debt, which means how much equity and how much debt will be used, so as to generat optimal capital structure. This study aims to examine the effect of propability, aset struktur, sales growth and size of the company’s capital srtuktur on manufacturing companies Listed in Indonesia Stock Exchange (BEI) in the year 2012-2014. The data used is data companies Listed on the Stock Exchange in the period 2012-2014. Researchers using purposive sampling and obtained a sample of 181 observation data. Analysis of data using multiple linier regression testing. The results showed that :Profitability negatif effect on the capital structure, asset structure does not effect the company’s capital structure, sales growth did not effect the company’s capital structure, the size of the company and significant positif effect on the company’s capital structure.Keywords: Profitability, Asset Structure, Sales Growth, Firm Size and Capital Structure